Erratum to: Light in the beam dump: Axion-Like Particle production from decay photons in proton beam-dumps - Döbrich, Babette; Jaeckel, Joerg; Spadaro, Tommaso (Journal of high energy physics, 2020)
We correct a number of figures in [1], in which the PYTHIA MC result of secondary π0 mesons was displayed wrongly due to a missing factor of 2. Scrutinizing the corrected data-MC comparsion, we review and model the trigger condition used in the LEBC-EHS experiment, and present an improved data-MC comparison.